Effects of CeO_2 nanoparticles on microstructure and properties of laser cladded NiCoCrAlY coatings - 王宏宇 左敦稳 黎向锋 陈康敏 黄铭敏 (Journal of rare earths, 2010)
CeO2 nanoparticles(nano-CeO2p) were added into laser cladded NiCoCrAlY coatings on Ni-based superalloy substrate to improve the microstructure and properties.Scanning electron microscope(SEM),X-ray diffractometer(XRD),micro-hardness tester,and heat treatment furnace were employed to investigate their morphologies,phases,micro-hardness and thermal shock resistance,compared with the coating without nanoparticles added.The results showed that the microstructure and properties of the coatings with the addition ...